The Influences of Competence, Burnout and Work-Life Balance on Organizational Citizenship Behavior and Performance of Employees PT. Haleyora Power ULP Bangkalan - Gina Imaningtyas; Ida Aju Brahmasari; Ida Aju Brahma Ratih (PT Inovasi Pratama Internasional, 2024)
This study aims to determine and analyze the effects of competence, burnout, and work-life balance on organizational citizenship behavior and employee performance at PT. Haleyora Power ULP Bangkalan. The approach used in this research is a quantitative approach. The data collection technique used a questionnaire distributed to all employees with a total of 113 employees. The data analysis technique used is the Structural Equation Modeling (SEM) method. by using a tool in the form of statistical software, namely AMOS 24: (1) Competency has a positive and significant effect on Organizational Citizenship Behavior, (2) Competency has a positive and significant effect on Employee Performance, (3) Burnout has a negative and significant effect on Organizational Citizenship Behavior, (4) Burnout has a negative and significant effect on Employee Performance, (5) Work-Life Balance has an insignificant effect on Organizational Citizenship Behavior, (6) Work-Life Balance has an insignificant effect on Employee Performance, (7) Organizational Citizenship Behavior has a positive and significant effect on Employee Performance.